Influence of the mold type on the mechanical properties of the piston alloy with nano alumina in casting and metal mold - Al-Zuhairi, Haitham Mohammed Ibrahim; Alshalal, Iqbal; Abtan, Auday Awad; Mahdi, Baha Sami; Asmail, Muna Khalil (Eastern-European Journal of Enterprise Technologies, 2022)
This research is an experimental comparison study to show the influence of mold type casting on mechanical properties. The study considers the aluminum alloy of a gasoline engine piston with nanoparticles alumina Al2O3 size 25 nm manufactured in two types of molds. Sand mold and cast-iron mold were selected to cast the aluminum composite components. A systematic comparative study of tensile strength and hardness properties of cast aluminum components is made on sand and metal molds production. The nano powder can add to enhance the mechanical properties must not exceed 4 % for metal and sand mold casting. According to data for hardness, adding nano alumina powder has minimal impact on metal mold casting, but it significantly improves sand casting. From a financial standpoint, metal casting provides higher economic values for making piston aluminum castings. The hardness rises as the alumina content does in two molds as compared to the obtained specimen. It demonstrates that the highest hardness occurs at 4 % alumina in the sand-casting mold and at 6 % alumina in the metal. When the compositions of the casting materials are the same, a comparison of the fracture morphology between sand and mold casting reveals more ductile fractures for metal molds compared to brittle fractures in sand cast by large silicon separation grains because of higher grain growth in sand casting by longer solidification time. The same is seen in mold casting, which exhibits reduced ductility due to the alumina nanoparticles’ dispersion strengthening process in the aluminum matrix. This arises as a result of nano alumina dispersion acting as barriers to dislocation motions in the aluminum matrix, enhancing strength but reducing ductility.